Pengaruh Green Intellectual Capital Index, Biaya Corporate Social Responsibility, dan Green Accounting terhadap Kinerja Keuangan Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi - Raissa, Manda Azalia Nur; Rahmatika, Dien Noviany; Firmansyah, Fahmi (Universitas Syiah Kuala, 2025)
From 2020 to 2024, this study explores the effects of Green Intellectual Capital, Corporate Social Responsibility costs, and Green Accounting on financial performance. The research uses data from mining companies listed on the Indonesia Stock Exchange and treats company size as a moderating variable. A quantitative methodology is adopted for this study, which relies on secondary data. Multiple linear regression analysis is the primary method used to examine the data, which was collected from the firms' annual and sustainability reports. The findings of this research are anticipated to highlight the significance of Green Intellectual Capital management, CSR investments, and Green Accounting implementation in boosting financial performance. Furthermore, the study examines the moderating role of company size on the relationships between these variables, providing valuable strategic recommendations for fostering sustainable business practices within the mining sector. This research should contribute to the field of sustainability and provide a roadmap for companies to enhance their financial performance with eco-friendly practices.